O KŁOPOTACH NAUCZYCIELA Z MATERIAŁEM LEKSYKALNYM PODRĘCZNIKÓW DO NAUCZANIA JĘZYKA POLSKIEGO JAKO OBCEGO – NA WYBRANYCH PRZYKŁADACH - Badyda, Ewa (Neofilolog, 2019)
The article discusses the problems concerning vocabulary introduced in some popular contemporary coursebooks for Polish language teaching. What can be sometimes found in them are words and expressions not suiting the language level of the course, some of them rare, specialized, obsolete, marked in a characteristic way, regional. It also happens that words are used improperly in the context or they are consolidated in unnatural linguistic contexts. Also some problems with proper names appear – they sometimes have a confusing form or, with no good reason, they are very difficult to pronounce. The situation is partly the result of the authors’ efforts made to simplify grammar or introduce humorous atmosphere during the lesson. In the conclusion the author suggests paying more attention to the choice of vocabulary units to be taught.